A study protocol to develop and assess the utility of a Dinacharya habit-tracking mHealth app towards modification of health behaviour of study subjects - Kumar, Sadhna; Kuchewar, Vaishali (International Journal of Clinical Trials, 2025)
Background: Dinacharya (daily regimen) in Ayurveda are health practices that sync with circadian rhythms, and promote holistic health. Mobile health apps (mHealth) are widely adopted tools of behavioural change communication to implement health behaviours. However, there is still significant scope for mHealth research in Ayurveda. In particular, there is a noticeable lack of high-quality, authentic, educational and interactive habit-tracking apps based on Dinacharya principles. The objective of this study is to develop and assess the utility of Dinacharya Habit-Tracking mHealth App on the health behavior of subjects. Methods: The study has 3 parts: design and validate Dinacharya guidelines and Dinacharya KAP questionnaire (Delphi method); develop a habit-tracking Dinacharya app and multimedia database, and assess the app’s effectiveness on health behaviour outcomes of the study subjects with a prospective randomized controlled trial. 72 healthy volunteers, aged between 18 to 65 years, English speaking and mobile literate will be recruited. Participants will be randomized into the trial group receiving the app intervention (n=36) and the control group receiving Dinacharya printed material intervention (n=36), for 4 weeks. Primary outcomes include frequency of habit adoption, and knowledge, attitudes and practice of Dinacharya. Secondary outcomes include objective and subjective assessment of feasibility, usability, navigation, motivation, and overall rating via the Mobile app rating scale (MARS) and semi-structured interviews, respectively. The outcomes will be assessed at baseline, week 1, week 2, week 3, and post-intervention. Conclusions: The findings from this study will offer empirical data on the effectiveness of mHealth in promoting healthy habits, and educating users about Dinacharya. Findings may guide development of future Ayurveda-based apps by demonstrating how digital tools can support user engagement and integrate traditional wellness principles into modern healthcare. Trial Registration: CTRI-Clinical Trial Registry of India (CTRI/2025/06/089328).